Huge extramedullary hematopoiesis mass in the posterior mediastinum: a case report - Zhao Junjun; Dong Lingjun; Ma Zhifeng; Zhang Chu; Wang Haiyong (Frontiers in Oncology)
BackgroundExtramedullary hemopoiesis (EMH) is a rare condition characterized by abnormal blood cell production outside the bone marrow, commonly occurring in the liver, spleen, lymph nodes, and less frequently in the mediastinum.Case presentationThis case involves a 68-year-old male patient who was found to have a posterior mediastinal mass upon examination. A surgical biopsy was performed, and pathological examination confirmed it to be extramedullary hemopoiesis (EMH). Further investigation revealed that the patient also suffered from hemolytic anemia.ConclusionsThe report presents a case of a large posterior mediastinal mass, which was confirmed to be extramedullary hemopoiesis (EMH) upon surgical pathology. It is challenging to differentiate posterior mediastinal tumors from EMH, and the possibility of EMH should be considered in patients with posterior mediastinal masses that have similar CT findings and laboratory test results.